2022
DOI: 10.29114/ajtuv.vol6.iss1.258
|View full text |Cite
|
Sign up to set email alerts
|

Drone-based Monitoring of Sunflower Crops

Abstract: Remote monitoring and utilization of digital technologies is essential for the application of the precision farming approach, which contributes significantly to the improved quality of agricultural products. The paper compares the data for six vegetation indices when observing the sunflower vegetation in South Dobrudzha in 2021. Images with RGB and digital NIR camera were obtained via a remotely piloted quadcopter. The flight plan specifies speed 8 m/s, altitude 100 m and shooting overlapping images of 80%. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Atanasov et al [41] presented a cultivator-based method for measuring soil density. Soil density measurement can be carried out using a cultivator with a strain gauge fitted to each working body.…”
Section: Methods and Equipment For Determining Soil Compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atanasov et al [41] presented a cultivator-based method for measuring soil density. Soil density measurement can be carried out using a cultivator with a strain gauge fitted to each working body.…”
Section: Methods and Equipment For Determining Soil Compactionmentioning
confidence: 99%
“…These researchers also evaluated the effect of tillage depth on soil physical properties and found that deep tillage (>20 cm) resulted in lower penetration resistance, lower soil bulk density, higher soil air-filled pore volume, and higher soil hydraulic conductivity [52]. The water content of the soil has a strong influence on the measurement of soil density as one of the key factors for planning appropriate agrotechnical measures [41].…”
Section: The Effect Of Variable Depth Tillagementioning
confidence: 99%